TASKS TO BE IMPLEMENTED IN THE PROCESS OF FORMING THE ECONOMIC CULTURE OF FUTURE SPECIALISTS (Academia Science Repository, 2023)
Youth activity is the criterion of our prosperous life. In this sense, we should pay serious attention to the education of young people. Youth education is the sacred duty of every parent, teacher and educator to the Motherland. In the conditions of transition to market relations, the solution of socio-economic, political, cultural and moral problems in higher education institutions is becoming an urgent task.